1999
DOI: 10.1111/1468-2389.00121
|View full text |Cite
|
Sign up to set email alerts
|

Interim Managers: Distinguishing Personality Characteristics of Managers on Short‐term Contracts

Abstract: The use of interim managers by companies is increasing, and reasons for this trend are discussed. A study is reported in which the normative personality make-up of a group of interim managers is compared with that of a general sample of UK managers. Ninety-four interim managers completed the revised PA Preference Inventory (PAPI-N) and the results are compared with those from a general UK managerial sample. Statistically significant differences are reported for 12 out of 20 scales, with nine of the effect size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…During the last decade, one of the fastest growing aspects in human resource management has been in the area of personality testing as employees are selected based on whom best fits the required profile (Rolfe & McPherson, 1995). One issue closely related to staffing is the growing trend in the outsourcing of selected aspects of management via short-term contracts (Feltham & Hughes, 1999). This research would allow corporation to better match the short-term organizational needs with appropriate personality types.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, one of the fastest growing aspects in human resource management has been in the area of personality testing as employees are selected based on whom best fits the required profile (Rolfe & McPherson, 1995). One issue closely related to staffing is the growing trend in the outsourcing of selected aspects of management via short-term contracts (Feltham & Hughes, 1999). This research would allow corporation to better match the short-term organizational needs with appropriate personality types.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness involves being dependable, careful, thorough, responsible, organized, planful, hardworking, achievement-orientated and persevering (Barrick and Mount, 1991). Feltham and Hughes' (1999) quantitative cross-sectional study found that interims had higher scores on the traits needed to finish a task and integrative planning (both facets of conscientiousness; Woods and Anderson, 2016) and are typically more conscientious than permanent managers. Müller and Turner's (2007) mixed-methods analysis found that conscientiousness was one of three significant contributors (along with sensitivity and communication skills) to project success across all projects explored and was important throughout the project life cycle.…”
Section: Individual Characteristics Of Effective Interim Leadership: Fulfilling the Assignment Cyclementioning
confidence: 99%
“…Mooney et al ., 2017; Browning and McNamee, 2012; Inkson et al ., 2001; Goss and Bridson, 1998; Farquhar, 1995). Yet, we know comparatively little in research about the individual characteristics of effective interim leadership relative to permanent leadership, despite evidence of their potential distinctiveness (Feltham and Hughes, 1999). To address this need, this paper provides a narrative review of the literature on interim leadership and management in order to draw out emergent themes, to set directions for future research and identify practical implications for human resource (HR) management.…”
mentioning
confidence: 99%
“…"Geçici Yönetim", 1970'li yıllarda Hollanda'da işverenlerin işten çıkarılan işçilere kıdem tazminatı ödemek zorunda kaldıkları iş kanunundan kaçabilmek için oluşturdukları bir seçenektir. Hollanda'da uygulanan Geçici Yönetim'in daha sonra Birleşik Krallık'ta popülerliğinin arttığı görülmüştür (Feltham ve Hughes, 1999). "Geçici Yönetim", 1980'li yılların başından itibaren Almanya'da da uygulanmaya başlanmış ilk dikkat çeken atılım olarak da Alman Özelleştirme Ajansı tarafından başlatılan Geçici Yöneticilerin kararlarına göre şirket birleşmelerinde rol oynamıştır (Bruns, 2005, s. 514-515).…”
Section: Geçici Yönetim Ve Geçici Yöneticiunclassified